The Role of Health Workers in Comprehensive Midwifery Care for High-Risk Pregnant Women: Peran Tenaga Kesehatan Pada Asuhan Kebidanan Komprehensif Dengan Ibu Hamil Risiko Tinggi - Rena Oki Alestari; Ivana Devitasari; Neneng Safitri; Nita Kusuma (KHD Production, 2025)
Comprehensive midwifery care is comprehensive midwifery management care starting from pregnant women, giving birth, to newborns so that labor can take place safely and babies are born safe and healthy until the postpartum period. There are still many high risk pregnancies, high risk pregnancies include 4T and 3T, too young, less than 20 years old and too old, more than 35 years old. The high risk of being pregnant too late > 35 years can cause hypertension/high blood pressure, preeclampsia, LBW and fetal defects. The service method uses health education using lectures, questions and answers, and monitoring the condition of high-risk pregnant women using leaflets and giving stickers to high-risk pregnant women at home. The activity will be held on June 20 2024, at RT.01 Bejarau. The results of this community service activity can be said to be successful. This can be observed by pregnant women who are at risk receiving information about the impact on their pregnancy and pregnant women can be monitored by health workers, so that they can reduce MMR and IMR. The follow-up that needs to be done is to continuously provide comprehensive care to pregnant women as an early detection of high risks in pregnancy.